Новый вид слизистых споровиков (Myxosporidia) от черноморской тонкорылой рыбы-иглы - Каратаев, А.К. (Вестник зоологии, 1983)
Chloromyxum osmanovi sp. n. is described from gall bladder of Syngnathus tenuirostris Rathke, 1837. Spores spheric, 5.8-65X5.6-6.0 um, sporal valvae smooth, polar capsules pyriform, equal, 1.3-16X1.1-14 um.